A deep dive into Avivore. Issue 8 (August 2020) - Fay, Oliver
Abstract : Until now, most prominent supply chain intrusions have been vertical attacks, with the initial victims typically managed service providers (MSPs) or vendors targeted as a way of getting into and moving up or down the supply chain. However, incidents earlier this year targeting large multi-national firms in the aerospace and defence sectors can best be described as horizontal. Advanced attackers have been leveraging relationships and connectivity between suppliers and partners to get a foothold in each other's value chains. However, recent incidents targeting large multi-national firms in aerospace and defence can best be described as horizontal. Attackers have leveraged connectivity between suppliers and partners to get a foothold in each other's value chains. Oliver Fay of Context Information Security details a new threat group, codenamed Avivore, that has been compromising collaborative working solutions to bypass well-defended perimeters.